029 Clinical decision rules for children with minor head injury: a systematic review. (14th September 2011) - Pickering, A; Harnan, S; Fitzgerald, P; Pandor, A; Goodacre, S
Abstract : Objectives and Background: Clinical decision rules aid clinicians with the management of head injured patients. This study aimed to identify clinical decision rules for children with minor head injury and compare their diagnostic accuracy for detection of intracranial injury (ICI) and injury requiring neurosurgical intervention (NSI). Methods: Relevant studies were identified by an electronic search of key databases. Papers in English were included with a cohort of at least 20 children suffering minor head injury (GCS 13–15). Studies of a decision rule derived to identify patients at risk of ICI or NSI had to include a proportion of the cohort undergoing imaging. Study quality was assessed using the QUADAS checklist. Results: 16 publications, representing 14 cohorts, with 79 740 patients were included. Only four rules were tested in more than one cohort. Of the validated rules the paediatric emergency care applied research network (PECARN) rule was most consistent (sensitivity 98%; specificity 58%). For neurosurgical injury all had high sensitivity (98–100%) but the children's head injury algorithm for the prediction of important clinical events (CHALICE) rule had the highest specificity (86%) in its derivation cohort. The positive predictive value (PPV) for each rule were calculated. Of the large cohorts studied (>10 000 subjects) CHALICE had PPV of 5.4% compared with 2.0% for PECARN for ICI. For NSI the PPV calculated were 4.2% and 0.4% respectively. Conclusion: Of the current decision rules for minor head injury the PECARN rule appears the best for children and infants, with the largest cohort, highest sensitivity and acceptable specificity for clinically significant ICI. Application of this rule in the UK would probably result in an unacceptably high rate of CT scans per injury, and continued use of the CHALICE- based NICE guidelines represents an appropriate alternative.